The Flouting of Conversational Maxims by Male and Female Characters in the British TV Series Broadchurch - Andrian Yonathan Damanik; Sharifah Hanidar (Universitas Gadjah Mada, 2021)
This research focuses on examining the flouting of the Gricean conversational maxims on the British TV series Broadchurch. It also investigates the use of rhetorical strategies in flouting the maxims by male and female characters in the series. The research data were the utterances that flout the maxims. The data were collected from Season I of the Series, containing 8 episodes. The data were analyzed by applying Grice’s theory of cooperative principle (1975). Moreover, the data were also analyzed in terms of the rhetorical strategies employed by the characters when they flout the maxims. The results show that 97 cases of maxim flouting were found. The characters most frequently flout the maxim of relation (44.33%) and least frequently the maxim of quality (13.40%). Furthermore, in flouting the maxims, male characters tend to use the irrelevant statements as their preferred rhetorical strategy (63.46%), whereas female characters tend to use obscure expressions as their preferred rhetorical strategy (33.33%).